Opłacalność produkcji pszczelarskiej w Polsce - Majewski, Janusz; Madras-Majewska, Beata (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2004)
The article treats about bee keeping which is a very important element of agriculture. The most important role of bees in environment is plants pollination. Bee colonies produce honey, propolis, bee wax and bee bred. The situation in bee keeping in Poland was critical in the middle of the eighties. The number of apiaries decreased 4 times whereas the number of bee hives decreased 3 times by the end of the nineties. The biggest problems of Polish bee keeping are small average number of trunks in the apiary as well as beekeepers age. They are usually older people and are keeping bees as a hobby. Almost 60% of apiaries have only 20 bee colonies. Such apiaries cannot become the base of beekeeper family livelihood. Only beekeepers that have at least 1 OO colonies in and out apiary can get income high enough to fully support their families. They also have to sell honeybees' products directly to customers. Based on estimations and calculations authors state that Polish bee keeping has a chance to develop in the future. On one hand Polish beekeepers have a chance to get subsidies from EU as well as from Polish government. On the other hand they also have a possibility to gain profits selling their products.